Mathematical model of CPM/PERT network in project management using taylor's expansion - Ten, Wei Peng (Terengganu: Universiti Malaysia Terengganu, 2012)
Failure to complete a project management either by the original planned time or budget, or both, ultimately results in project delays. Project delays may caused by a number of changes in a project, including late completion, loss of possible early completion, or acceleration of the work. Finally, the relationship among the owner, project manager, project team, project sponsor, vendors, suppliers, client and others can be negatively affected by the disputes, claims, abandonment, or termination resulting from delays.